Conjuntos de controle e controlabilidade de sistemas bilineares - Nayene Michele Pitta Paião (2009)
In this work we studied the problem of the controllability bilinear system of the form x' = Ax + uBx, where the A and B are matrices in sl(n, R) satisfying conditions of Jurdjevic and Kupka, and u is the control, real unrestricted. The approach of the problem will be made by theory of control set for action of semigroups in compact homogeneous manifolds and, more particularly, in Grassmannianas manifolds